Stability analysis for two-layered slopes by using the strength reduction method - Sourav Sarkar; Manash Chakraborty (International Journal of Geo-Engineering, 2021)
Abstract The aim of this article is to present the slope stability charts for two layered soil slopes by using the strength reduction method (SRM). The primary focus is to provide a quantitative estimation of the improvement of slope stability when a stronger layer is placed over the weaker layer. The SRM carried in this work comprises a series of finite element lower bound (LB) and upper bound (UB) limit analysis in conjunction with nonlinear optimization. Unlike the limit equilibrium method (LEM), there is no need to consider any prior assumptions regarding the failure surface in SRM. The study is carried out for different combinations of (i) slope angles (β), (ii) strength properties of the top and the bottom layer (c, ϕ) and (iii) different thickness of the top layer. The failure patterns are shown for a few cases.